Characterization of Novel Dipeptidyl Peptidase-IV Inhibitory Peptides from Soft-Shelled Turtle Yolk Hydrolysate Using Orthogonal Bioassay-Guided Fractionations Coupled with In Vitro and In Silico Study - Nhung Thi Phuong Nong; Yu-Kuo Chen; Wen-Ling Shih; Jue-Liang Hsu (MDPI AG, 2020)
Five novel peptides (LPLF, WLQL, LPSW, VPGLAL, and LVGLPL) bearing dipeptidyl peptidase IV (DPP-IV) inhibitory activities were identified from the gastrointestinal enzymatic hydrolysate of soft-shelled turtle yolk (SSTY) proteins. Peptides were isolated separately using reversed-phase (RP) chromatography in parallel with off-line strong cation exchange (SCX) chromatography followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis to determine sequences. Among these peptides, LPSW showed the highest DPP-IV inhibitory activity with an IC50 value of 269.7 ± 15.91 µM. The results of the pre-incubation experiment and the kinetic study of these peptides indicated that WLQL is a true inhibitor and its inhibition toward DPP-IV is of an uncompetitive model, while LPLF, LPSW, and VPGLAL are real-substrates and competitive inhibitors against DPP-IV. The DPP-IV inhibitory peptides derived from SSTY hydrolysate in study are promising in the management of hyperglycemia in Type 2 diabetes.